Handbook of research on cloud and fog computing infrastructures for data science - Chelliah, Pethuru Raj ca. 20./21. Jahrhundert; Raman, Anupama C. (Advances in computer and electrical engineering (ACEE) book series, 2018)
"This book explores cloud and fog/edge infrastructures for achieving next-generation data science functionalities and facilities. It also focuses on cloud infrastructures (public, private and hybrid) and edge/fog infrastructures that facilitate the formation and sustenance of device clouds in order to have powerful data science facility in place"...